The Effect of Price Perception and Discount Strategy on Customer Satisfaction and Customer Loyalty - Ida Ayu Trisna Wijayanthi; Ida Bagus Angga Brahmanta; Tettie Setiyarti (Malaqbi Publisher, 2026)
This study aims to examine the effect of price perception and discount strategy on customer satisfaction and customer loyalty, with customer satisfaction serving as a mediating variable. In today’s competitive business environment, pricing and promotional strategies play a crucial role in influencing consumer behavior and long-term relationship sustainability. This research adopts a quantitative approach using a cross-sectional survey design. Data were collected from 268 respondents who had experience purchasing products or services involving discount promotions within the last six months. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both direct and indirect relationships among variables. The results indicate that price perception and discount strategy have positive and significant effects on customer satisfaction. Furthermore, price perception, discount strategy, and customer satisfaction significantly influence customer loyalty. Among these variables, customer satisfaction demonstrates the strongest effect on customer loyalty. Mediation analysis reveals that customer satisfaction partially mediates the relationship between price perception and customer loyalty, as well as between discount strategy and customer loyalty. These findings highlight the importance of balancing fair pricing and strategic discount programs to enhance customer satisfaction, which ultimately fosters sustainable customer loyalty. The study contributes to marketing literature by integrating pricing perception and promotional strategy within a comprehensive loyalty framework and provides managerial insights for developing effective pricing and relationship marketing strategies.